2023
DOI: 10.1038/s41587-022-01628-0
|View full text |Cite
|
Sign up to set email alerts
|

Genome-scale metabolic reconstruction of 7,302 human microorganisms for personalized medicine

Abstract: The human microbiome influences the efficacy and safety of a wide variety of commonly prescribed drugs. Designing precision medicine approaches that incorporate microbial metabolism would require strain- and molecule-resolved, scalable computational modeling. Here, we extend our previous resource of genome-scale metabolic reconstructions of human gut microorganisms with a greatly expanded version. AGORA2 (assembly of gut organisms through reconstruction and analysis, version 2) accounts for 7,302 strains, incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
146
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3
3

Relationship

0
10

Authors

Journals

citations
Cited by 138 publications
(148 citation statements)
references
References 96 publications
2
146
0
Order By: Relevance
“…Considering such close interaction, it is logical to assume that microbiota influence host gene expression in all body areas that it colonizes, such as skin, respiratory organs, gastrointestinal, and urogenital tract. Two main mechanisms allow the microbiota to “regulate” our genome: through direct body exposure to microorganisms [ 21 ] or those of their metabolites [ 18 , 22 ]. Indeed, we must recognize a fine distinction between microbial antigen-mediated genome modulation and metabolite-mediated one [ 19 ].…”
Section: Resultsmentioning
confidence: 99%
“…Considering such close interaction, it is logical to assume that microbiota influence host gene expression in all body areas that it colonizes, such as skin, respiratory organs, gastrointestinal, and urogenital tract. Two main mechanisms allow the microbiota to “regulate” our genome: through direct body exposure to microorganisms [ 21 ] or those of their metabolites [ 18 , 22 ]. Indeed, we must recognize a fine distinction between microbial antigen-mediated genome modulation and metabolite-mediated one [ 19 ].…”
Section: Resultsmentioning
confidence: 99%
“…We use the Constrained Riemannian Hamiltonian Monte Carlo (RHMC), which has recently been shown to be substantially more efficient than prior sampling algorithms 41 .…”
Section: Methodsmentioning
confidence: 99%
“…These models have been used to estimate metabolic exchanges between pairs of bacterial species for over a decade 12,13 . Developments in automating the reconstruction of GEMs 14 , manually curating GEMs for thousands of gut microorganisms 15,16 , and in the availability of tools to model interactions between multiple species 17 have paved the way to build metabolic models for complex microbial communities. Studies using community-wide metabolic models have found dozens to hundreds of significantly different metabolic exchanges in the gut microbiome associated with type 2 diabetes 18 and in inflammatory bowel disease 19 when compared to healthy controls.…”
Section: Introductionmentioning
confidence: 99%